The effect of Setarud (IMODTM) on angiogenesis in transplanted human ovarian tissue to nude mice - Maryam Hormozi; Saeed Talebi; Hamid Reza Khorram Khorshid; Amir-Hassan Zarnani; Koorosh Kamali; Mahmood Jeddi-Tehrani; Haleh Soltangoraee; Mohammad Mehdi Akhondi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: One of the promising methods in fertility preservation among women with cancer is cryopreservation of ovarian cortex but there are many drawbacks such as apoptosis and considerable reduction of follicular density in the transplanted ovary. One solution to reduce ischemic damage is enhancing angiogenesis after transplantation of ovarian cortex tissue. Objective: The aim of this study was to investigate the effect of Setarud, on angiogenesis in transplanted human ovarian tissue. Materials and Methods: In this case control study, twenty four nude mice were implanted subcutaneously, with human ovarian tissues, from four women. The mice were randomly divided into two groups (n=12): the experimental group was treated with Setarud, while control group received only vehicle. Each group was divided into three subgroups (n=4) based on the graft recovery days post transplantation (PT). The transplanted fragments were removed on days 2, 7, and 30 PT and the expression of Angiopoietin-1, Angiopoietin-2, and Vascular endothelial growth factor at both gene and protein levels and vascular density were studied in the grafted ovarian tissues. Results: On the 2nd and 7th day PT, the level of Angiopoietin-1 gene expression in case group was significantly lower than that in control group, while the opposite results were obtained for Angiopoietin-2 and Vascular endothelial growth factor. These results were also confirmed at the protein level. The density of vessels in Setarud group elevated significantly on day 7 PT compared to pre-treatment state. Conclusion: Our results showed that administration of Setarud may stimulates angiogenesis in transplanted human ovarian tissues, although further researches are needed before a clear judgment is made.